Social distance in nineteenth-century etiquette handbooks: the case of the cut 'truncation' (Altre Modernità, 2023)
In historical politeness studies Discernment covers the compulsory adherence to the symbolic vertical axis posed by social hierarchy. Here I examine the horizontal dimension of Discernment in light of the compartmentalisation of social distance.The essay uses a manual and qualitative analysis, based on a corpus of 92 etiquette manuals from the long nineteenth century (1800-1920), consisting of sources in American English, British English, French, Italian and Dutch, all downloaded from digital libraries.The degree of social intimacy allows to distinguish three groups: relatives and close friends, acquaintances, and, finally, strangers. Access rituals such as the letter of introduction and in-person introductions put decision-making firmly in those who are socially superior. Furthermore, there are procedures for undoing an earlier presentation. In the Anglo-American world, the ‘cut’ consists of ‘not recognising’ the person who has been presented previously. Aware of crosscultural differences, some Italian women writers clearly grasp the fact that the ‘cut’ represents a rare opportunity for women to independently manage their social circle.The meticulous etiquette separating acquaintances from strangers demonstrates that the mandatory scope of Discernment affects social distance until well into the twentieth century. Discernment has a horizontal dimension as well as a vertical one.
Keywords: Discernment; politeness; etiquette; social distance; horizontality; nineteenth century